A measurement of the distance to the Galactic centre using the kinematics of bar stars. Issue 1 (6th December 2022) - Leung, Henry W; Bovy, Jo; Mackereth, J Ted; Hunt, Jason A S; Lane, Richard R; Wilson, John C
ABSTRACT: The distance to the Galactic centre R 0 is a fundamental parameter for understanding the Milky Way, because all observations of our Galaxy are made from our heliocentric reference point. The uncertainty in R 0 limits our knowledge of many aspects of the Milky Way, including its total mass and the relative mass of its major components, and any orbital parameters of stars employed in chemo-dynamical analyses. While measurements of R 0 have been improving over a century, measurements in the past few years from a variety of methods still find a wide range of R 0 being somewhere within 8.0 to 8.5 kpc . The most precise measurements to date have to assume that Sgr A* is at rest at the Galactic centre, which may not be the case. In this paper, we use maps of the kinematics of stars in the Galactic bar derived from APOGEE DR17 and Gaia EDR3 data augmented with spectrophotometric distances from the astroNN neural-network method. These maps clearly display the minimum in the rotational velocity vT and the quadrupolar signature in radial velocity vR expected for stars orbiting in a bar. From the minimum in vT, we measure R_0 = 8.23± 0.12 kpc . We validate our measurement using realistic N -body simulations of the Milky Way. We further measure the pattern speed of the bar to be Ω _bar = 40.08± 1.78 km s^-1 kpc^-1 . Because the bar forms out of the disc, its centre is manifestly the barycentre of the bar+disc system and our measurement is therefore one of the most robust and accurate measurements of R 0 to date.